Cooperativismo, capital social e desenvolvimento local: o caso da COAPROCOR de Corumbataí do Sul e região - Silva, Tiago Martins da (2013)
This dissertation has the main objective to study the importance of organization agricultural cooperative in the strengthening of the social capital and in the process of the sustainable urban development in Corumbataí do Sul. Since the cooperative in the process of formation and strengthening of the social capital, and also as a principal element in the formation of confidence ties with the rural worker. Beyond the importance for the sustainable development of the rural society, the cooperatives also contributes for the associate in two big dimensions; the economic shown through of the improvement in income and the social by promotion of knowledge and well-being of the associate. Is this context, was done a biographical research about cooperative, place development and social capital, as well as a field research together with the associates of COAPROCOR for to value and to demonstrate if cooperative contributes for the local development in Corumbataí do Sul and for the social capital strengthening between the associates.